2023
DOI: 10.3390/vaccines11030684
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to CoronaVac and Its Safety in Patients with Type 2 Diabetes Compared with Healthcare Workers

Abstract: Background: Vaccines for SARS-CoV-2 have been critical for preventing disease. Previous research showed patients with diabetes have impaired immunity. This study aimed to determine the immunity to coronavirus after CoronaVac by comparing patients with type 2 diabetes (T2D) and healthcare workers (HCW). Materials and methods: A prospective cohort study evaluated immune responses and safety after two doses of CoronaVac in T2D and HCW groups at Chulabhorn Hospital. The levels of total antibodies against the recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…also observed that fatigue (2.2% (2/89)) was the most common adverse event in DM patients who received the second dose of inactivated vaccine ( 35 ), Dechates et al. found that fatigue (11.1% (3/27)) was common side effects in DM patients who finished the full vaccination ( 24 ). However, the sample size was small and the adverse effects of DM patients who received partial and booster vaccination were not evaluated in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also observed that fatigue (2.2% (2/89)) was the most common adverse event in DM patients who received the second dose of inactivated vaccine ( 35 ), Dechates et al. found that fatigue (11.1% (3/27)) was common side effects in DM patients who finished the full vaccination ( 24 ). However, the sample size was small and the adverse effects of DM patients who received partial and booster vaccination were not evaluated in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…For the vaccinated coverage rate with at least one dose was 21.4% in India ( 20 ) and 31.0% in Sudan ( 21 ). The main reasons for vaccine hesitancy among DM patients are concern about the side effects and the safety of the COVID-19 vaccine ( 16 , 18 , 21 , 22 ), although the side effects of COVID-19 vaccine have been reported to be mild and self-limiting in DM patients ( 23 , 24 ). As a result, there are still obstacles for DM patients to receive the COVID-19 vaccine, which brings a great challenge to controlling the COVID-19 pandemic due to a higher prevalence of DM and a lower vaccination intention.…”
Section: Introductionmentioning
confidence: 99%